Young children learning about well-being and environmental education in the early years: a funds of knowledge approach. Issue 1 (2nd January 2016) - Edwards, Susan; Skouteris, Helen; Cutter-Mackenzie, Amy; Rutherford, Leonie; O'Conner, Mandy; Mantilla, Ana; Morris, Heather; Elliot, Sue
Abstract : Early childhood educators currently provide content focused learning opportunities for children in the areas of well-being and environmental education. However, these are usually seen as discrete content areas and educators are challenged with responding to children's interests in popular-culture inspired food products given these influence their consumption of energy-dense, nutrient-poor and highly packaged food in the early childhood setting. This paper reports preliminary findings from a pilot randomised trial examining the interconnectedness of sustainability, well-being and popular-culture in early childhood education. Planning, assessment documentation and summaries from twenty-four learning experiences implemented by six educators over a six-week period were analysed using a deductive approach. Twenty well-being and environmental education topics were identified and shown to be generated by the educators when considering the children's 'funds of knowledge' on popular-culture inspired food products. We argue that topics derived from children's engagement with popular-culture may help educators to create an integrated approach to curriculum provision. This may impact child weight and facilitate obesity prevention and environmental sustainability as children create stronger connections between these content areas and their everyday choices and practices.